Birds and other wildlife of south central Texas : a handbook - Kutac, Edward A. (Corrie Herring Hooks series, 1994)
Nature takes a surprising turn in the heart of Texas. The flat Gulf Coastal Plains, which become the fertile Blackland Prairies in Central Texas, end abruptly at the Balcones Escarpment, one of the state's most dramatic geological features, and the rolling, more sparsely vegetated Hill Country begins. The animal life varies as dramatically as the land. More than 400 species of birds alone, nearly three-fourths of all Texas birds, have been found in the region. This.